Development of dense models of the Earth’s surface based on the semiglobal matching method for the case of multiple overlapping images - Verkeenko, M. S.; Gorbachev, V. A. (Journal of computer & systems sciences international, 2017)
A method is developed for constructing a three-dimensional digital surface model based on the use of aerial images with multiple overlapping. The specific feature of this study is the use of the multiview matching method instead of stereo matching. The method is based on adapting the energy aggregation algorithm, which was proposed in the semiglobal matching (SGM) method, to the object space, as well as using the one-to-many scheme of cost calculation. The reconstructed scene is represented as a voxel grid. A high-performance implementation of the digital surface model construction at all stages is proposed based on the massive parallelization of computations on a graphics processing unit.